2017
DOI: 10.3389/fpubh.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

Integration of HIV Testing into Maternal, Newborn, and Child Health Weeks for Improved Case Finding and Linkage to Prevention of Mother-to-Child Transmission Services in Benue State, Nigeria

Abstract: BackgroundIn Nigeria, maternal, newborn, and child health (MNCH) weeks are campaign-like events designed to accelerate progress toward Millennium Development Goals. The authors examined whether integrating HIV testing into MNCH weeks was feasible and could lead to increased case finding and linkage to prevention of mother-to-child transmission (PMTCT) services.MethodsPregnant women attending MNCH week during the first week of December 2014 in 13 local government areas in Benue State were provided with HIV test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…One explanation for this comes from a report from Uganda in which having multiple partners was found to be a barrier to engagement in couples-based services because of the risk of positive results that made their spouses threatening. 22,23 There have been studies conducted in Africa that have shown usually high rates of positive HIV test results in countries such as Nigeria (2.1% in females 24 ) and Mozambique (5% in males, 18% in females 25 ). While the studies in Thailand have found the rates have been 0.5% in the period between 1999-2008 and 0.4% in 2009-2010, these were concordant infection.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this comes from a report from Uganda in which having multiple partners was found to be a barrier to engagement in couples-based services because of the risk of positive results that made their spouses threatening. 22,23 There have been studies conducted in Africa that have shown usually high rates of positive HIV test results in countries such as Nigeria (2.1% in females 24 ) and Mozambique (5% in males, 18% in females 25 ). While the studies in Thailand have found the rates have been 0.5% in the period between 1999-2008 and 0.4% in 2009-2010, these were concordant infection.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates are reported in Nigeria (6%) [3]; in Cameroon (7.6%) [4]. In contexts of low levels of consumption of prevention of motherto-child transmission services.…”
Section: Discussionmentioning
confidence: 91%
“…With the increasing coverage of HIV screening, the new directions of the World Health Organization and the Joint United Nations Program on HIV/AIDS rely on the implementation of a surveillance conducted among pregnant women attending prenatal consultations, based on data collected from the PTME program [2,3]. Benin has a national strategic plan to eliminate mother-to-child transmission, having made available 946 PTME sites in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of HIV testing into maternal, newborn and child health (MNCH) “weeks” (biannual campaign‐style events designed to expand health service access) may also be promising. In a single week, across 13 local government areas in Nigeria’s Benue State, more than 50,000 pregnant women were educated about HIV testing and >99% subsequently underwent testing via an opt out approach [54]. Risk stratification and other triage strategies should be used to increase the efficiency of such testing approaches in identifying pregnant women living with HIV.…”
Section: Resultsmentioning
confidence: 99%